Seasonal Fluctuation of the Population and Characterization of Bacillus spp. Isolated from the Coastal Soils of Digha, West Bengal, India. (12th May 2016) - Azmi, Syed Afrin; Chatterjee, Soumendranath
Abstract : Seasonal fluctuation of the population of Bacillus spp. in the coastal soils of Digha, West Bengal, India, was determined and it has been found that, during summer, monsoon, and winter season, the Bacillus population density varied in the range of 0.01–0.236 × 10 6, 0.11–0.202 × 10 6, and 0.098–0.155 × 10 6, respectively. Two-way ANOVA, agglomerative hierarchial cluster (AHC) analysis, and principal component analysis (PCA) were performed to determine the diversity of Bacillus spp. in both spatial and temporal aspects. During summer season, the population of Bacillus spp. reached a comparatively higher density than monsoon or winter. Spatial variation was also exhibited among the Bacillus spp. in different coastal villages. A total of 25 strains of Bacillus spp. (DSB1–DSB25) were isolated from the coastal soils of different village areas of Digha, during the study period. The isolates were characterized morphologically, physiologically, and biochemically. Colony morphology of each of the isolates was thoroughly studied. Biochemical tests along with fermentation tests, NaCl, pH, and temperature tolerance tests were done. The antibiotic sensitivity of the isolated Bacillus spp. against different standard antibiotics was also assessed. The study revealed that the coastal soils of Digha area were rich in different strains of Bacillus spp. showing significant differences in the morphophysiological and biochemical properties.